Complementary exams in the diagnosis of american tegumentary leishmaniasis - Ciro Martins Gomes; Natália Aparecida de Paula; Orlando Oliveira de Morais; Killarney Ataíde Soares; Ana Maria Roselino; Raimunda Nonata Ribeiro Sampaio (Sociedade Brasileira de Dermatologia, 2014)
The diagnosis of American Tegumentary Leishmaniasis is a difficult but essential task when considering the high toxicity profile of the drugs available. Since the discovery of its etiologic agent, numerous diagnostic tests have been developed. None of the tests available today can be considered as the gold standard, since they do not add enough accuracy for the disease detection. Good epidemiological and clinical knowledge of the disease are fundamental precepts of the dermatology practice and precede the rational use of existing diagnostic tests. In this article we aim, through extensive literature review, to recall fundamental concepts of any diagnostic test. Subsequently, based on this information, we will weave important comments about the characteristics of existing diagnostic tests, including immunological tests such as Montenegro's skin test, serology and detection of parasites by direct examination, culture or histopathology. Finally we will discuss the new technologies and options for the diagnosis of Cutaneous Leishmaniasis. The molecular biology technique is considered a promising tool, promoting the rapid identification of the species involved. We also aim to educate dermatologists about a disease with high morbidity and assist in its difficult recognition.